2012
DOI: 10.1371/journal.pone.0046208
|View full text |Cite
|
Sign up to set email alerts
|

Khz (Fusion of Ganoderma lucidum and Polyporus umbellatus Mycelia) Induces Apoptosis by Increasing Intracellular Calcium Levels and Activating JNK and NADPH Oxidase-Dependent Generation of Reactive Oxygen Species

Abstract: Khz is a compound derived from the fusion of Ganoderma lucidum and Polyporus umbellatus mycelia that inhibits the growth of cancer cells. The results of the present study show that Khz induced apoptosis preferentially in transformed cells and had only minimal effects on non-transformed cells. Furthermore, Khz induced apoptosis by increasing the intracellular Ca2+ concentration ([Ca2+]i) and activating JNK to generate reactive oxygen species (ROS) via NADPH oxidase and the mitochondria. Khz-induced apoptosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In addition, our previous study demonstrated that Khz induces apoptosis by increasing intracellular calcium levels and activating c-Jun N-terminal kinase and NADPH oxidase-dependent generation of ROS (22). These findings suggested that Khz induces apoptosis in A549 human lung cancer cells by generating reactive oxygen species and decreasing the mitochondrial membrane potential (23).…”
Section: Discussionmentioning
confidence: 85%
“…In addition, our previous study demonstrated that Khz induces apoptosis by increasing intracellular calcium levels and activating c-Jun N-terminal kinase and NADPH oxidase-dependent generation of ROS (22). These findings suggested that Khz induces apoptosis in A549 human lung cancer cells by generating reactive oxygen species and decreasing the mitochondrial membrane potential (23).…”
Section: Discussionmentioning
confidence: 85%
“…This mushroom has been widely used as a herb for the promotion of health and longevity in Asian countries. There have been reports on the biological activities including histamine release-inhibitory action [25], immunomodulatory activity [11], anti-tumour cytokine production [10], differentiation-inducing activity [26], and activity to induce cancer cell apoptosis and inhibition of cancer cell death [27][29]. Ganoderma lucidum has been widely used by patients with different types of cancers that are too advanced for surgery, chemotherapy, or radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“… Kim et al (2012) in an effort to prove the anti-inflammatory effect of Vitis amurensis found out that excitotoxicity was induced not only by NMDARs but also due to the depletion of GSH levels and lipid peroxidation. MAPKs, cyclooxygenase-2 (COX-2), and pro-apoptotic proteins were also found to be active in these neurons.…”
Section: Cell Lines Models Utilized For the Study Of Glutamate-inducementioning
confidence: 99%